PS-R05-6: A CASE OF ACUTE KIDNEY INJURY WITH THROMBOTIC MICROANGIOPATHY CAUSED BY MALIGNANT HYPERTENSION. (January 2023) - Nakagawa, Terumasa; Shimasaki, Akiko; Miura, Rei; Inoue, Hideki; Minami, Shogo; Ko, Takehiro; Izumi, Yuichiro; Kuwabara, Takashige; Adachi, Masataka; Kohda, Yukimasa; Mukoyama, Masashi
Abstract : A 31-year-old man was transferred to our hospital because of severe hypertension, acute kidney injury (AKI) and thrombotic microangiopathy (TMA). A month earlier, the patient sought medical attention for epigastric pain. Upper gastrointestinal endoscopy revealed hemorrhagic gastric ulcer, and hemostasis was performed. At that time, his was found to have severe high blood pressure (200/140 mmHg), together with low levels of hemoglobin (Hb) (10.5 g/dL) and platelet (Plt) count (107 x 109/L). One week later, gastric ulcer tended to improve, but the blood pressure was still high (192/122 mmHg), along with severe abnormalities in creatinine (Cr) (10.7 mg/dL), Hb (6.6 g/dL) and Plt levels (139 x 109/L). On the following day, the serum Cr level increased to 13.7 mg/dL, while Hb and Plt levels decreased to 6.3 g/dL and 111 x 109/L, respectively. He was referred and admitted to a local affiliated hospital. Because the patient was considered as AKI due to dehydration and anemia, fluid replacement and blood transfusion were performed. However, his renal function was worsened further and pulmonary congestion appeared, which required initiation of hemodialysis therapy. Because low platelet counts, high LDH levels and schistocytes in peripheral blood were observed, he was diagnosed with TMA and transferred to our hospital. Laboratory data on admission revealed as follows: the plasma renin activity (PRA), 7.8 ng/ml/h, plasma aldosterone concentration (PAC), 443 pg/mL, plasma adrenaline, 12 pg/mL, noradrenaline, 172 pg/ml, ACTH, 17.3 pg/mL, cortisol, 6.9 g/dL, and TSH, 1.71 IU/mL. Renal artery stenosis was not observed by renal artery ultrasound. Echocardiography showed hypertrophy of the left ventricle. Funduscopic examination showed retinal hemorrhages. Renal biopsy revealed a large number of collapsed glomeruli, onion skin lesions in the arterioles and interlobular arteries, luminal narrowing due to thrombosis, and fibrin accumulation on the blood vessel walls, which lead to histological diagnosis of malignant nephrosclerosis and TMA. Intensive treatment with a calcium channel blocker, an ACE inhibitor, and other antihypertensive agents resulted in improved hypertension, and normalized platelet count and LDH levels, together with reduced PRA (3.2 ng/ml/h) and PAC (208 pg/mL). However, withdrawal from hemodialysis was not achieved. We consider that in this case TMA was caused by malignant hypertension due to essential hypertension. We conclude that early detection and intervention for hypertension are mandatory to prevent the progression of malignant hypertension and related organ damages.